Utilization of FISH in positional cloning: an example on 13q22. - Laan, M; Isosomppi, J; Klockars, T; Peltonen, L; Palotie, A (Genome Research, 1996)
In positional cloning the initial assignment of a gene to a specific chromosomal locus is followed by physical mapping of the critical region. The construction of a high-resolution physical map still involves considerable effort. However, new high-resolution fluorescence in situ hybridization (FISH) techniques have facilitated this process substantially. Here we summarize a strategy that combines a spectrum of FISH techniques [metaphase, interphase, mechanically stretched chromosomes (MSCs), and fiber-FISH on free chromatin] for the construction and characterization of a high-resolution physical map for a positional cloning project. The chromosomal region 13q22, containing the locus of the variant form of the neuronal ceroid lipofuscinosis (vLINCL, CLN5) disease, serves here as an example for this process. We used metaphase FISH to exclude positionally a candidate gene, to refine the locus to 13q22, and to analyze the possible chimerism of the YACs in the region. Both metaphase and interphase FISH techniques were applied to determine the low-resolution distances between the restricting markers. FISH using MSCs confirmed the centromeric-telomeric order of the clones and facilitated the estimation of the size of the gaps between the clones. Finally, fiber-FISH was found to be the method of choice for the construction of an accurate high-resolution map of the contig established over the restricted region. Thus, FISH techniques in combination with genetic mapping data enabled the refinement of the initial 4-cM region to a high-resolution map of only 400 kb in length. Here the FISH strategy replaced the need for many laborious traditional physical mapping methods, e.g., pulsed-field gel electrophoresis.